2000
DOI: 10.1002/1099-1352(200011/12)13:6<360::aid-jmr508>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

New feature of angiotensin‐converting enzyme: carbohydrate‐recognizing domain

Abstract: Self carbohydrate-mediated dimerization of glycoprotein angiotensin-converting enzyme (ACE) was demonstrated. The dimerization was studied in the reverse micelle experimental system as a model of biomembrane situation. Asialo-ACE or agalacto-ACE was able to form a dimer, whereas deglycosylated ACE and sequentially desialylated and degalactosylated ACE failed to dimerize. ACE-ACE interaction was competitively inhibited by Neu5Ac- or Gal-terminated saccharides. The results have allowed us to propose the existenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 13 publications
(20 reference statements)
2
22
0
Order By: Relevance
“…Our observation of sACE dimerization in mammalian cells confirms previous studies that showed sACE dimerization in synthetic biomembranes, in crosslinking investigations, and in a Saccharomyces cerevisiae split-ubiquitin assay (Kost et al, 2000(Kost et al, , 2003Kohlstedt et al, 2006). However, to our knowledge, this is the first time that tACE dimerization has been described (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our observation of sACE dimerization in mammalian cells confirms previous studies that showed sACE dimerization in synthetic biomembranes, in crosslinking investigations, and in a Saccharomyces cerevisiae split-ubiquitin assay (Kost et al, 2000(Kost et al, , 2003Kohlstedt et al, 2006). However, to our knowledge, this is the first time that tACE dimerization has been described (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Previously, different interactions were proposed to be involved in dimerization. Dimerization of human sACE in reverse micelles was inhibited in the presence of galactose and it was suggested that a carbohydrate recognition domain in the N domain of sACE (Ndom) mediates dimerization (Kost et al, 2000). Alternatively, sACE active site mutants overexpressed in porcine aortic endothelial cells showed that a catalytically active C domain was required for dimerization and initiation of signaling (Kohlstedt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that mAb 3G8 inhibited proteolytic cleavage of ACE from the cell surface is especially interesting. Recently it was shown that somatic ACE can form dimers in artificial membrane preparations (reverse micelles) and this process was inhibited effectively by several carbohydrates, including galactose [37]. We have found that, among our set of anti-ACE antibodies, only two mAbs, which are directed to overlapping but not identical epitopes, 3G8 and 9B9 [20], inhibited dimer formation in micelles.…”
Section: Discussionmentioning
confidence: 80%
“…Soluble forms of somatic and testicular ACEs were isolated from bovine lung and bovine testicles, respectively, by Triton X‐100 extraction and were further purified by lisinopril affinity chromatography as described in [12]. Membrane form of somatic ACE was isolated from bovine lung by Triton X‐100 extraction in the presence of 1 mM EDTA as described in [13]; the enzyme was purified by hydrophobic and affinity chromatography according to [14].…”
Section: Methodsmentioning
confidence: 99%